Coagulation, deformability, and aggregation of RBCs and platelets following exposure to dielectric barrier discharge plasma with the use of different feeding gases. (8th February 2019) - Kim, Jeongho; Ghimire, Bhagirath; Lim, Sinye; Choi, Eun Ha; Park, Hun-Kuk; Kaushik, Nagendra Kumar
Abstract: There are several applications for non-thermal plasma at atmospheric pressure, such as the sterilization of infected tissues, wound healing, and delicate surgery. Non-thermal plasma generates reactive oxygen/nitrogen species (RONS). In this study, we examined human red blood cells (RBCs), platelet function, and blood coagulation, following treatments with different feeding gases (air, nitrogen (N2 ), and argon (Ar)) of the dielectric barrier discharge plasma (DBDP) at different exposure times. This is the first study to evaluate the effects of DBDP on hemolysis, deformability, aggregation, and morphology of RBCs, as well as platelet function and blood coagulation at three doses (5, 10 and 15 min exposure). In comparison to N2 and Ar DBDP, air DBDP at more than 10 min exposure to RBC in culture plate with 2 ml liquid solution caused hemolysis and alterations in RBC deformability and aggregation owing to the higher levels of hydrogen peroxide, hydroxyl oxidants and other RONS. Moreover, air DBDP affected platelet function at high doses (more than 10 min exposure). Consequently, the air DBDP at, or more, than 10 min exposure affects blood coagulation and blood cells. The proposed method is useful for assessing the performances and dose optimization of various non-thermal plasma types used with different type of gases in biological applications.